1992
DOI: 10.1111/j.1540-8159.1992.tb02935.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Vagus Nerve Stimulation Increases the Latency of the Thalamocortical Somatosensory Evoked Potential

Abstract: The Neurocybernetic Prosthesis (NCP) is a pacemaker-like device that has been designed to provide chronic intermittent vagus nerve stimulation. It is currently under study for the treatment of refractory partial onset epilepsy, and preliminary studies have indicated that partial onset seizures are improved by this therapy. The mechanisms by which it exerts its antiepileptic effect are not well understood. Although there are extensive pathways to the forebrain from the nuclei of the vagus nerve, the evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(18 citation statements)
references
References 22 publications
1
15
0
2
Order By: Relevance
“…So far, investigation of evoked potentials in humans undergoing VNS has not produced consistent results. Although a prolongation of the latency of the N 2 0 peaks of median nerve somatosensory evoked potentials has been reported (Naritoku et al, 1992), other studies failed to reproduce any alteration of somatosensory-, visual-, or auditory-evoked potentials (Hammond et al, 1992a,b). Nevertheless, the influence of VNS on brain activity has been shown by imaging studies using positron emission tomography, single photon emission computed tomography, or FMRI techniques Narayanan et al, 2002;Sucholeiki et al, 2002;Vonck et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…So far, investigation of evoked potentials in humans undergoing VNS has not produced consistent results. Although a prolongation of the latency of the N 2 0 peaks of median nerve somatosensory evoked potentials has been reported (Naritoku et al, 1992), other studies failed to reproduce any alteration of somatosensory-, visual-, or auditory-evoked potentials (Hammond et al, 1992a,b). Nevertheless, the influence of VNS on brain activity has been shown by imaging studies using positron emission tomography, single photon emission computed tomography, or FMRI techniques Narayanan et al, 2002;Sucholeiki et al, 2002;Vonck et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Data pertaining to safety, tolerability, quality of life, and long-term efficacy are reported in subsequent articles (George et al, 1994;Ramsay et al, 1994). Preliminary results related to efficacy (George and Michael, 1991;Ramsay et al, 1991), safety , electrophysiologic aspects (Hammond et al, 1990;Martin et al, 1991;Naritoku et al, 1991;Hammond et al, 1992a,h), and cerebrospinal fluid (CSF) changes (Ben-Menachem et a]., 1991) were reported previously.…”
mentioning
confidence: 86%
“…Long‐term VNS had no effect on interictal EEG background or epileptiform activity and no effect on visual and auditory evoked potentials (7,8). One report showed an increase in N13–N20 interpeak interval with prolonged VNS (9).…”
mentioning
confidence: 97%
“…The precise mechanism of action of VNS is not entirely clear. Previous investigators have attempted to characterize the mechanism of action of VNS by using EEG and evoked potentials, cerebrospinal fluid (CSF) neurochemistry, and functional imaging (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). CSF studies have shown a significant increase in ␥-aminobutyric acid (GABA) after 3 to 4 months of VNS, but no significant decrease in glutamate, aspartate, or 5-hydroxyindoleacetic acid (5-HIAA) levels after 3 and 9 months of VNS treatment.…”
mentioning
confidence: 99%